MEDIA EDUKASI DIGITAL UNTUK PROMOSI CANDI PENATARAN SEBAGAI UPAYA PENGEMBANGAN PARIWISATA BUDAYA - Holil, Munawar (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
The development of cultural tourism greatly depends on the appreciation and involvement of the community in preserving and maintaining their cultural assets. However, over time, public awareness and concern for cultural heritage have gradually declined. One site that holds high historical and cultural value is Candi Penataran, a relic from the Majapahit era that has been recognized as an important cultural and historical tourism destination in Indonesia. Candi Penataran possesses significant tourism potential. In addition to its historical value as a cultural heritage, its strategic location along the same route as the tomb of Indonesia’s Proclaimer, Ir. Soekarno, provides a major opportunity to attract visitors. The site is also easily accessible, as it is reachable by public transportation and located near a main road. Situated at the foot of Mount Kelud, the area enjoys a cool climate and offers beautiful rural scenery, surrounded by agricultural lands that dominate the landscape. Recognizing this potential, this community service program aims to strengthen the tourism appeal of Candi Penataran through information digitalization and community empowerment. The digitalization of information will make it easier for visitors to access the history and cultural significance of Candi Penataran. Meanwhile, training local residents to create promotional content is expected to enhance their capacity to independently and sustainably promote their tourism site.